Apparent digestibility coefficients of feed ingredients for black carp, Mylopharyngodon piceus - Tran Quang Hung (2018)
The apparent digestibility coefficients of dry matter, crude protein, crude lipid, ash, and gross energy in five test ingredients - fishmeal, meat and bone meal, soybean meal, cornmeal, and brewers yeast (Saccharomyces cerevisiae) - were determined for black carp, Mylopharyngodon piceus (78.3±2.5g), at the Aquaculture Laboratory, Vietnam National University of Agriculture, Vietnam. A reference diet and test diets (a 70:30 mixture of the reference diet to test ingredient) were used with 1% chromic oxide (Cr 2 O 3 ) as an external indicator. Experimental fish were stocked in 500-L composite tanks at a density of 10 fish per tank. Faeces were collected by faecal collection column. The results indicated that the apparent digestibility coefficients of all test ingredient nutrients, except ash, differed statistically (P < 0.05). The apparent digestibility coefficients were 78.4-90.2% for dry matter, 71.2-92.6% for crude protein, 66.0-87.0% for crude lipid, 52.6-61.9% for ash, and 54.1-80.9% for gross energy. Findings from this study will help formulate cost-effective feed for black carp.